Perlindungan Hukum terhadap Peserta Vaksin Covid-19 atas Data Pribadi yang disalahgunakan oleh Tenaga Kesehatan - Made Gama Sasmitha; I Nyoman Putu Budiartha; I Nyoman Subamia (Jurnal Interpretasi Hukum, 2022)
This study aims to analyze and describe the legal protection for COVID-19 vaccine participants for personal data misused by health workers. During the Covid-19 pandemic, the government carried out an evenly distributed vaccination program throughout Indonesia. However, in the process there were several mistakes made by health workers and the leaking of personal data from the vaccine participants in the Peduli Protect.id application. this violates the rights of vaccine participants by contacting vaccine participants personally that is not related to the vaccination process. The author uses the journal is normative legal research. The results of the discussion show that this is a prohibited act so that the form of legal protection regarding personal data has specifically been regulated in Articles 30-35 of the Electronic Information and Transaction Law so that administrative sanctions and civil lawsuits can be charged to perpetrators due to misuse of personal data. The author suggests that the government should be more active regarding the establishment of a regulation concerning the protection of the private data of its people.